Goals and games designing your employee's goals like game designers design video games - Edery, David 1976- (FTPress Delivers, 2010)
"This Element is an excerpt from Changing the game: how video games are transforming the future of business (ISBN: 9780132357814) by David Edery and Ethan Mollick. Apply the lessons of game design to supercharge employee productivity, performance, creativity, and satisfaction!"--Resource description page.